2020
DOI: 10.3329/birdem.v11i1.51028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin D and calcium alone or in combination in the treatment of nutritional rickets

Abstract: Background: Nutritional rickets has emerged as a public health problem in Bangladesh during the past two decades, with up to 8% of children being clinically affected in some areas. Insufficiency of vitamin D and dietary calcium is thought to be the underlying cause. Vitamin D administered with or without calcium is commonly regarded as the mainstay of treatment. Calcium alone or in combination with vitamin D has also been used in the treatment of nutritional rickets. So this study was done to assess the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Among the volunteers, only 55% breastfed their kids [12]. Early research in Bangladesh showed that lack of vitamin D was not a significant cause of the common rickets, and calcium lack is the main etiologic reason [20]. In terms of rickets complications, a majority (45.1%) reported delayed development, 15.5% had dental problems, 12.7% had seizures, 8.5% had bone deformities, 5.6% had scoliosis, and 1.4% had congenital heart anomalies.…”
Section: Table (4): Risk Factors Of Rickets Among Diagnosed Children ...mentioning
confidence: 99%
“…Among the volunteers, only 55% breastfed their kids [12]. Early research in Bangladesh showed that lack of vitamin D was not a significant cause of the common rickets, and calcium lack is the main etiologic reason [20]. In terms of rickets complications, a majority (45.1%) reported delayed development, 15.5% had dental problems, 12.7% had seizures, 8.5% had bone deformities, 5.6% had scoliosis, and 1.4% had congenital heart anomalies.…”
Section: Table (4): Risk Factors Of Rickets Among Diagnosed Children ...mentioning
confidence: 99%